Sự sáng tạo thúc đẩy kết quả công việc được giao và hành vi đổi mới của nhân viên: Vai trò điều tiết của trao quyền về mặt tâm lý. - Võ Thành, Đức; Trần Hà Minh, Quân; Lâm Đình, Thắng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This study examines the impact of employee creativity on both in-role performance and employee innovation. Concomitantly, this study examines the moderating role of employee psychological empowerment on these above relationships. Based on the data set of 430 employees, this study found that in-role performance mediated the relationship between employee creativity and employee innovation. Further, employee psychological empowerment moderated both the employee creativity-in-role performance relationship and the employee creativity-innovation relationship. These results contributed to the literature on employee creativity and innovation by exploring the moderating role of employee psychological empowerment in the relationship between employee creativity and its outcomes (i.e., in-role performance and innovation).